A model of information technology competencies towards high-tech firms performance through innovation capabilities and absorptive capacity - Abdul Raheem, Hayder Adil (2021)
Recognized as a knowledge-driven industry, the high-tech manufacturers’ sector contributes significantly to the Malaysian economy. Hence, High-Tech manufacturing firms must be innovative and remain sustainable. However, this industry is still less innovative than other countries in the region and developed countries because of several challenges. For example, most of the firms' use of information communication technology is relatively low with inefficient performance. The knowledge quality and utilization still form a big challenge to many of them. As a main player in industry 4.0 and in line with the national policy (Industry 4WARD), high-tech manufacturers are expected to undergo digital transformation to ensure innovativeness and sustainability. Information technology (IT) facilitates firms’ innovativeness by enhancing their absorptive capacity in flexible knowledge transform, assimilation and utilization. Yet, not all firms that use IT are innovative because it depends on IT competencies of the dynamic capabilities with respect to the high-tech manufacturers on effective use, the integration of IT functions and competencies in managing and developing firms’ innovativeness. This leaves an open gap that needs further investigation on how innovation capabilities can be enhanced through the effective utilization of IT competencies in high-tech manufacturers, especially in developing countries where the literature is scarce. A quantitative method was driven by a survey distributed to 274 high- tech manufacturers in four sectors, namely Aerospace, Pharmaceutical, Machinery and Equipment and Electric and Electronic sectors, to carry out this aim. Through employing Smart-PLS, the finding of this research shows that the unique and rare resources of IT competencies have a direct positive relationship with high-tech manufacturers’ innovation capabilities, but not their performance. Also, the finding shows that innovation capabilities and absorptive capacity fully mediates the relationship between IT competencies and manufacturers’ performance. In addition, the absorptive capacity through knowledge exploration, assimilation, transformation and exploitation play an effective mediating role in the relationship between IT competencies and innovation capabilities. The finding of this research brings new insight to the body of knowledge by providing a model that explains how IT competencies as resource-based view and absorptive capacity as dynamic capabilities influence several aspects of high-tech manufacturing firms' performance in developing countries. This model also provides a guide for the managers of high-tech manufacturing firms to achieve excellent innovation capability that contributes to the competitive advantage. Finally, this model contributes to the policymakers in the Malaysian government by providing them with a guide on how to attend the transformation of Malaysian industry 4.0 (4WARD).